PENERAPAN TEKNOLOGI PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA DENGAN MAGGOT PADA PROGRAM KAMPUNG IKLIM DI KOTA BUKITTINGGI - Rudi Febriamansyah; Fuji Astuti Febria; Yulistriani Yulistriani; Defri Rahman; Resti Rahayu; Mahdi Mahdi (LPPM Universitas Andalas, 2021)
This activity is motivated by concern for the facts of climate change occurring globally and regionally. In response to this, the Indonesian government has also taken a number of concrete steps in all aspects of climate change adaptation and mitigation, both at the local, regional, and national levels. One national program that directly touches local communities is the climate village program known as